PENERJEMAHAN METAFORA DALAM SAMAN KE DALAM BAHASA PRANCIS - Kuswarini, Prasuri; Masdiana, Masdiana; Hantik, Zulvyati (JURNAL ILMU BUDAYA, 2018)
Ayu Utami's novel Saman used many metaphors to express the messages to be conveyed. These metaphors are formed in various ways. Translation as a means of relaying the ST message into the TT must be able to transfer the messages that the metaphors convey equally. This article contains the result of research on the methods used to translate the metaphor in the Indonesian version of the Saman novel to the French version. The first phase of analysis was to make a classification of metaphor types in Saman of the Indonesian version. The second step, was to analyze the method used in translating themetaphor found in the French version of the novel. The results show that there are some unusual metaphors in the source language (SL). In general, the metaphor translated in French used literal methods of translation. Some translation errors are also found